Sleep quality and high intensity interval training at two different times of day: A crossover study on the influence of the chronotype in male collegiate soccer players. (7th February 2017) - Vitale, Jacopo A.; Bonato, Matteo; Galasso, Letizia; La Torre, Antonio; Merati, Giampiero; Montaruli, Angela; Roveda, Eliana; Carandente, Franca
ABSTRACT: The influence of the chronotype on the sleep quality in male collegiate soccer players in response to acute high intensity interval training (HIIT) performed at two different times of day was evaluated. The sleep quality was poorer in the morning-type than in the evening-type players after the evening HIIT session, whereas no significant changes in the sleep quality of the two chronotypes after the morning HIIT session was observed. The results suggest that an athlete's chronotype should be taken into account when scheduling training sessions and to promote faster recovery processes.